Correlation Between the Use of Bengkung Towards Uterine Involution in Postpartum Mothers - Ester Yohana Sitorus; Sri Martini; Mahanani Mulyaningrum (LPPM AN NUUR, 2023)
Background: Uterine involution is the process of returning the uterus to its original state or pregnancy state. The postpartum periode (puerperium) begins after the birth of the placenta and ends when the uterine organs return to their pre-pregnancy state, the postpartum periode, there are many physical and psychological changes, where women continue to need care and protection, one of which is the use of bengkung. Purpose: To determine the relationship between the use of bengkung and uterine involution in postpartum women at PMB Nur Kusuma Grobogan. Method: This research method used is an analitic survey design. Population of all postpartum mothers at PMB Nur Kusuma. A sample of 30 respondents, namely 15 respondents in the intervention group and 15 respondents in the control group. Data analysis with Chi Square test. Results: The use of bengkung in postpartum mothers has the same proportion between those who use and do not use bengkung, the are 15 respondents (50%0 each. Most of the uterine involution of postpartum mothers was normal (5-6 cm TFU) in 22 respondents (73,3%)Conclusion: There is a relationship between the use of bengkung and uterine involution of postpartum women at PMB Nur Kusuma (p=0,013).